Pembuatan Jamu Tradisional Kunyit Asam KKN Universitas Aufa Royhan Padang Sidimpuan di Kelurahan Pintu Padang II - Sindi A. Nasution; Dina Amelia; Anni Safitra; Alia Safitri; Yeyen Herlena (CV. Alfa Pustaka, 2025)
The